Full transparency or control release of information as a dilemma of the contemporary PR crisis - Todorov, Sergey (Media and Language, 2022)
The use of the control release of information in today’s informational 21st century is a fact and some would say it is really a problem, if it is not used properly and only in particular spheres and under specific circumstances. Others would say that it serves as a weapon or a tool for achieving a communication purpose with certain risks. The most important in the case is that the use of such actions would show a certain actions, which were evolving in the past and that was never on the spotlight. And not only. The use of the tactics such as the control release of information is risky and could have huge and could have very heavy consequences for the communication. The control release of information is a process, used by the PR specialists to tell a certain information in a particular moment of time. The release of this information in most cases is aiming to deceive the public – it can be totally untrue, untrue and later on refuted by the PR, partially true or totally true. In the last two cases the reason is to study the public reaction for e specific intention of institution, agency, government, non government organisation. If there is no negative public reaction for the intention of the institution or organisation after the release of the information „the negative feedback“ in the communication is minimal. The control release of information is a tool in today’s PR crisis, which can be applied in different communicational situations and with different purposes. This is a tactics, that is meant to be used in the moments of crisis for the public organisation and to check in most cases anonymously and not directly connected with the organisation the public reaction for an intention of the organisation or to publish decieving information, which aims to distract the attention in another direction. It takes resourcefulness judging the right moment to apply the tactics. The risks for the organisation are not so big, because it can hardly be proved that is used. The reason is that are using media and the right of protect the source of information without discovering the name. In this case is very difficult to know who is the real source in information.